The Relationship of Between the Interactive Justice and Coworkers Justice with Depression symptoms )Field Study according six, years of experience and workplace). - Sbera, Fouad; Kahileh, Reem; Haydar, Rasha (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to identify The Relationship of Between Both of the Interactive Justice and Coworkers justice with Depression symptoms in a Sample of Teacher in Primary Education Schools. The Organizational Justice content (Distributive Justice, Procedural Justice, Interactive Justice).The study was conducted on a sample of teachers in the province of Latakia numbered (304) teachers, these teachers were (202) females, (102) males. In order to achieve the goal of this research, the researcher used scale of the Interactional Justice and Experiences ofcoworkers Justice scale, and depression demonstration scale. The researcher reached the following conclusions: There isn't any correlation between the interactional justice and depression symptoms among the members of the sample, but There isn't any correlation between coworkers Justice and depression symptoms among the members of the sample, there is no differences between males and females on the scale of interactive Justice in the sample of teacher, there is differences between males and females on the scale of coworkers in favor of females, there is no differences between the sample of teacher on the scale of depression symptoms